Gambaran Kadar Hemoglobin Pada Ibu Hamil Trimester III di Puskesmas Bandar Khalipah - Wiratma, Dicky Yuswardi; Kurniawan, Budi; Gunawan (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Anemia is a problem that is generally experienced by pregnant women, changes in the composition of the content also affect the body's metabolism. Pregnant women tend to get anemia due to increased circulation changes to the placenta and the fetus also accumulates iron reserves. In addition, the relationship between iron and anemia is also continuous with morbidity in pregnant women. Bleeding due to anemia is the main factor in maternal mortality, which is 31.25%. The type of research used in this study is descriptive analytic. This research was conducted at Bandar Khalipah Public Health Center from May to July 2022. This examination was carried out on 10 pregnant women using the Sahli method. Based on the results of the examination, it was found that 7 people (70%) Haemoglobin increased and 3 people (30%) others did not increase. Based on the results of the examination on pregnant women who have been given Fe tablets, it can be concluded that the increase in hemoglobin levels is due to consuming iron (Fe) tablets containing iron and folic acid. Meanwhile, the hemoglobin level did not increase even though they had consumed Fe tablets because pregnant women had not received a balanced intake and diet. Pregnant women can adjust their diet, take prenatal vitamins which usually contain iron and folic acid which are good for the blood and take Fe tablets so that hemoglobin remains stable during pregnancy.